2016
DOI: 10.2147/dddt.s87435
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated knockdown of NLK inhibits small-cell lung cancer growth and metastasis

Abstract: Nemo-like kinase (NLK), an evolutionarily conserved serine/threonine kinase, has been recognized as a critical regulator of various cancers. In this study, we investigated the role of NLK in human small-cell lung cancer (SCLC), which is the most aggressive form of lung cancer. NLK expression was evaluated by quantitative real-time polymerase chain reaction in 20 paired fresh SCLC tissue samples and found to be noticeably elevated in tumor tissues. Lentivirus-mediated RNAi efficiently suppressed NLK expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, misregulation of Nmo-like kinases in humans, namely an increase in Nmo levels, has been correlated with various cancers 80 , 81 , which together might suggest that Nmo generally regulates tissue fluidity and that dysregulation of tissue fluidity can have a negative impact in disease 54 , including cancer 73 . The unjamming transition has been proposed to resemble invasion of interstitial spaces by tumor cells, particularly those that are not dependent upon epithelial-mesenchymal transition 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, misregulation of Nmo-like kinases in humans, namely an increase in Nmo levels, has been correlated with various cancers 80 , 81 , which together might suggest that Nmo generally regulates tissue fluidity and that dysregulation of tissue fluidity can have a negative impact in disease 54 , including cancer 73 . The unjamming transition has been proposed to resemble invasion of interstitial spaces by tumor cells, particularly those that are not dependent upon epithelial-mesenchymal transition 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into gallbladder cancer demonstrated that NLK was upregulated in cancer tissues, which was associated with the poor prognosis of patients (28). Notably, Lv et al reported that increased NLK expression in SCLC could promote invasion and metastasis (29). Conversely, the present study observed reduced NLK expression in NSCLC; this may reflect the differential expression of NLK in organs, tissues and the internal environment of cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Lv et al 26 reported that low NLK expression was an independent prognostic factor for NSCLC patients’ low survival rate by multivariate analysis. However, Lv et al 27 revealed that lentivirus-mediated knockdown of NLK inhibits small-cell lung cancer growth and metastasis. These suggest that the same gene NLK may function differently in the location of histology and cytology.…”
Section: Discussionmentioning
confidence: 99%